2016
DOI: 10.1007/s10616-016-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

Promoting differentiation of cultured myoblasts using biomimetic surfaces that present alpha-laminin-2 peptides

Abstract: Traditionally, muscle cell lines are cultured on glass coverslips and differentiated to investigate myoblast fusion and differentiation. Efficient differentiation of myoblasts produces a dense network of myotubes with the correct organisation for contraction. Here we have tested the ability of artificially generated, precisely controlled peptide surfaces to enhance the efficiency of myoblast differentiation. We focused on specific short peptides from α-laminin-2 (IKVSV, VQLRNGFPYFSY and GLLFYMARINHA) as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…C2C12 myoblasts were seeded at the same cell density (1 × 10 5 cells/ml) on coverslips coated with laminin-1 (Sigma). After 24-h infection with adenovirus, the growth medium was exchanged for differentiation medium and the cells were incubated at 37 °C for 5 days to allow for differentiation into skeletal muscle myotubes, before being fixed as described [34] .…”
Section: Methodsmentioning
confidence: 99%
“…C2C12 myoblasts were seeded at the same cell density (1 × 10 5 cells/ml) on coverslips coated with laminin-1 (Sigma). After 24-h infection with adenovirus, the growth medium was exchanged for differentiation medium and the cells were incubated at 37 °C for 5 days to allow for differentiation into skeletal muscle myotubes, before being fixed as described [34] .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to gene expression, the effect of extracellular matrix components on differentiation and subsequent production by the cells can be studied in the future. Previous researchers reported that the laminin protein significantly promotes cell adhesion and differentiation of C2C12 cells 26,50,51 . Furthermore, we expect that these electrically active, nanotopographic crumpled graphene substrates can electrically stimulate cells.…”
Section: Resultsmentioning
confidence: 95%
“…Previously, we have demonstrated that peptide motifs can be presented to cells, by use of an engineered variant of outer membrane protein A (OmpA) as a scaffold protein for anchoring the motifs in a structurally intact, correctly orientated and highly functional manner as selfassembled monolayers (SAMs) [51,52]. This "ORLASurf®" technology has been used to generate biomimetic surfaces that can be used in cell culture applications, and have previously been shown to promote neural differentiation [53,54] and cellular adhesion [55], depending upon the ECM-derived motif presented to cells.…”
Section: Introductionmentioning
confidence: 99%